Cavitation & hydrodynamic performance of a propeller in a simulated ice-blocked flow - Walker, D.; Bose, N.; Yamaguchi, H. (1993)
Experiments were done on a 200mm diameter open propeller behind a similar ice blockage in a cavitation tunnel. The propeller performance in uniform flow and blocked flow is contrasted over a range of advance coefficients and at different cavitation numbers. Mean thrust and torque coefficients are presented. The types of cavitation, and its intermittent nature over a cycle of operation, are reported. The experiments indicate the likelihood of cavitation at full scale for blocked conditions and illustrate the effects of cavitation on mean values of thrust and torque. NRC publication: Yes